Evaluation method of the light-trapping structure for a transparent thin-film silicon solar cell with low-illuminance condition. (1st January 2022) - Choi, Soo-Won; Park, Jae-Ho; Kim, Ji-Hoon; Kim, Yonghun; Song, Pungkeun; Shin, Myunhun; Kwon, Jung-Dae
Highlights: Transparent solar cells were made for building-integrated photovoltaics (BIPV). Front electrode was etched with time to enhance light-trapping in absorption layer. High current was obtained in low light-trapping structure under low light intensity. Textured structure was considered to make entangled performance with light intensity. The rate equation clarified optical gain and electrical loss with light intensity. Abstract: Transparent hydrogenated amorphous silicon (a-Si:H) thin-film solar cells were fabricated for building-integrated photovoltaic (BIPV) windows, and light-trapping structures were formed on aluminum-doped zinc oxide (ZnO:Al) front electrodes to increase the output current and power under low-irradiance conditions in buildings. The degree of light-trapping was controlled by varying the etching time for texturing the ZnO:Al electrodes. As the etching time increased from 5 to 20 s, the surface area and average haze increased from 102.02 to 116.27 μm 2, and 3.4 to 14.6% in the absorption wavelength range of 400–600 nm, respectively. The introduction of the light-trapping structure can increase the photogenerated current but causes defects in the cell. The current and defect density both depend on the light intensity; the highest power conversion efficiency of the cell was obtained in different light-trapping structures depended on the light intensity. To evaluate the light-trapping effect independent of the light intensity, we theoretically derived the effective absorbance and current density loss parameters using rate equations, which were in good agreement with the measurements. The presented methods can be applied to various thin-film solar cells requiring light-trapping structures to effectively utilize low-illuminance conditions.